Implementation of Warm Compresses to Lower Body Temperature in Children with Denguehaemorrhagic Fever (DHF) Army Hospital Kindergarten IV 01.07.01 Pematang Siantar - Simbolon, Danti; Yohana, Yohana (CV. Devitara, 2024)
Dengue Haemorrhagic Fever (DHF) is a disease caused by the dengue virus, belonging to the Flaviviridae family and there are 4 sterotypes, namely DEN-1, DEN-2, DEN-3, and DEN-4. The design of this research is quantitative - descriptive using a case study approach. The research sample consisted of 2 respondents with the inclusion criteria of DHF children, using warm pediatric nursing assessment formats, thermometers, and temperature measurement observation sheets. The sampling used in this research was purposive sampling. Data was collected using observation techniques, interviews, physical examinations, supporting examinations, documentation carried out on April 23 2024 and June 27 2024 at the TK IV Army Hospital 01.07.01 Pematangsiantar. This research was conducted for 3 days. The results of the research that have been obtained confirm the nursing diagnosis, namely hyperthermia with warm compress intervention given 3 times a day for 3 days of treatment to client 1 which decreased to 36.5 0C and to client 2 it decreased to 360C. The main problem of hyperthermia in both clients was resolved by using warm compresses. Researchers , especially parents, are expected to be able to apply the warm compress technique as a measure to treat high fever in children who experience Dengue Haemorrhagic Fever (DHF), especially when caring for sick children at home apart from giving antipyretics.